Abnormal urethral pathways in a child presenting with diphallia - Dylan John Kendrick; Lucy Erin Goddard; Roy Mark Kimble (Elsevier, 2021)
Diphallia is an extremely rare embryological anomaly, occurring once in 5-6 million births. Here we discuss a neonate who was referred for surgical consultation of diphallia, in which examination revealed a dominant right phallus and apparently shorter left phallus. MRI and retrograde urethrogram revealed a unique pathway of the right urethra and a stenosed, but otherwise normal left urethra. The decision was made to excise the right phallus and associated urethra due to the correct anatomy of the left phallus and corresponding urethra.